2018
DOI: 10.3390/ijms19051478
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Induces Apoptosis and Alters Cellular Responses to Oxidative Stress in Ht29 Colon Cancer Cells: Preliminary Findings

Abstract: Accumulating evidence suggests that metformin, used as an antidiabetic drug, possesses anti-cancer properties. Metformin reduced the incidence and growth of experimental tumors in vivo. In a randomized clinical trial among nondiabetic patients, metformin treatment significantly decreased the number of aberrant crypt foci compared to the untreated group with a follow-up of 1 month. In our study, HT29 cells were treated with graded concentrations of metformin, 10 mM/25 mM/50 mM for 24/48 h. We performed immunofl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 52 publications
3
45
0
1
Order By: Relevance
“…The anti-cancer property of metformin is not fully examined. However, some reports indicate the induction of autophagy and apoptosis among patients with colon cancer, one of the most common entities in oncology [ 225 ]. Metformin pharmacotherapy is related with cell cycle arrest in the G0–G1 phase [ 226 ].…”
Section: Oxidative Stress Parkinson’s Disease and Cancermentioning
confidence: 99%
“…The anti-cancer property of metformin is not fully examined. However, some reports indicate the induction of autophagy and apoptosis among patients with colon cancer, one of the most common entities in oncology [ 225 ]. Metformin pharmacotherapy is related with cell cycle arrest in the G0–G1 phase [ 226 ].…”
Section: Oxidative Stress Parkinson’s Disease and Cancermentioning
confidence: 99%
“…(53) Sena et al also demonstrated that metformin has an antiproliferative effect relevant to changes in the expression of Nuclear factor E2-related factor 2 (NRF-2)/NF-κB pathways, additionally an apoptotic effect on human colon cancer cells. (54) Numerous studies have indicated that the antitumour effect of metformin may be due to a relationship between metformin and immune cells. In another study metformin inhibited IL-6-induced epithelial-mesenchymal transition signalling by inhibiting STAT3 phosphorylation in colon cancer lines.…”
Section: Other Mechanismsmentioning
confidence: 99%
“…In the colon carcinoma cell line HT29, MTF induced both autophagy and apoptosis. On the molecular level, MTF increased, in a time- and dose-dependent manner, protein expression of apoptotic peptidase activating factor 1 (APAF1), cleaved poly (ADP-ribose) polymerase 1 (PARP1), autophagosomal marker microtubule associated protein 1 light chain 3 (MAPLC3), and CASP3 while decreasing expression of nuclear factor, erythroid 2 like 2 (NFE2L2; alias, NRF2) and nuclear factor-kappa B (NFKB) [ 82 ].…”
Section: Pleiotropic Mtf Effects On Cancer: Basic and Preclinicalmentioning
confidence: 99%